4‐Bromo‐Butyric Acid‐Assisted In Situ Passivation Strategy for Superstable All‐Inorganic Halide Perovskite CsPbX3 Quantum Dots in Polar Media. Issue 22 (25th March 2022) - Zhu, Hong; Pan, Yuexiao; Peng, Chengdong; Lian, Hongzhou; Lin, Jun
Abstract: A crucial challenge is to develop an in situ passivation treatment strategy for CsPbX3 (CPX, X=Cl, Br, and I) quantum dots (QDs) and simultaneously retain their luminous efficiency and wavelength. Here, a facile method to significantly improve the stability of the CPX QDs via in situ crystallization with the synergistic effect of 4‐bromo‐butyric acid (BBA) and oleylamine (OLA) in polar solvents including aqueous solution and a possible fundamental mechanism are proposed. Monodispersed CsPbBr3 (CPB) QDs obtained in water show high photoluminescence quantum yields (PLQYs) of 86.4 % and their PL features of CPB QDs have no significant change after being dispersed in aqueous solution for 96 h, which implies the structure of CPB QDs is unchanged. The results provide a viable design strategy to synthesize all‐inorganic perovskite CPX QDs with strong stability against the attack of polar solvents and shed more light on their surface chemistry. Abstract : A facile method to significantly improve the stability of the CsPbX3 (CPX) QDs via in situ crystallization with synergistic effects of BBA and OLA in polar solvent is proposed. The results not only provide a viable design strategy to synthesize all‐inorganic perovskite CPX QDs with strong stability against the attack of polar solvents but also shed more light on their surface chemistry.